Is A Combination of Antibiotics and Non-Steroidal Anti-Inflammatory Drugs More Beneficial Than Antibiotic Monotherapy For The Treatment of Female Acute Uncomplicated Cystitis? A Randomized Controlled Pilot Study - Ko, Kyungtae; Lee, Won Ki; Oh, Cheol Young; Lee, Seong Ho; Cho, Sung Tae; Bang, Woo Jin; Shin, Tae Young; Choo, Min Soo; Cho, Jin Seon; Lee, Young Goo; Yang, Dae Yul (Urology Journal, 2018)
Purpose: To compare the efficacy of non-steroidal anti-inflammatory drugs (NSAIDs) combination therapy to single-agent antibiotic therapy for the resolution of symptoms during two restricted activity days in patients with acute uncomplicated cystitis (AUC) Materials and Methods: We performed a prospective, randomized control pilot study. A total of 55 patients were enrolled. Group I (n=28) was treated with cepodoxime (100 mg twice per day), and Group II (n=27) was treated with cepodoxime (100 mg) and aceclofenac (100 mg) twice per day; both groups were treated for three days. Upon dysuria after each administration, the participants entered a value on a numerical pain scale. The primary outcome was whether there were any differences in the decrease rate in pain scale between the two groups. Result: The average age of the 55 patients was 49.9 ± 13.5 years, and prior to the clinical visit, the patients experienced an average of 2.4 ± 2.2 days of dysuria symptoms. The average numerical pain scale score for dysuria was 4.98 ± 2.18. Thirty-four patients (61.8%) showed positive culture results, and E. coli was the most commonly found bacteria, cultured in 32 patients. Fifty-one patients visited the clinic on day 7, and 42 (76.4%) reported symptom improvement, while nine patients (16.3%) had persistent symptoms. The follow-up numerical pain score was 0.39 ± 1.02 points. The pain score was dramatically decreased after medication. No difference was observed in the magnitude of the pain scale reduction between the two groups (P = 0.134). However, group II showed faster symptom resolution (P = 0.035) at the third administration (day 1.5). Conclusion: Combination therapy with NSAIDs and antibiotics for AUC patients can improve symptoms faster during two restricted activity days when patients have difficulty performing daily living activities.